War or health? assessing public health education and the potential for primary prevention - White, Shelley K.; Lown, Bernard; Rohde, Jon E (© 2013 Public Health Reports, 2017)
This review was published in The Public Health Reports [© 2013 Public Health Reports] and the definite version is available at: https://www.ncbi.nlm.nih.gov/pmc/articles/PMC3804102/